Proses Quality Control Product Drag Link pada Kendaraan Roda Empat di PT. Indo Integral Sekawan - Aqil Achmad Fadilah (Jurnal Sosial Teknologi, 2026)
Quality Control on Drag Link parts at PT. Indo Integral Sekawan is one of the production processes in the manufacturing sector. PT. Indo Integral Sekawan is a manufacturing company in the automotive sector. One of them is producing Drag Link. The results of the study show that this company has implemented an effective Quality Control system, including the selection of raw materials, inspection during the production process, and the packing process that will be sent to customers. However, several challenges were found in the consistency of the implementation of quality standards, namely Data analysis revealed that the product defect rate was 2%. With the most common types of defects being dimensional mismatches and surface defects. Based on these findings, it is recommended to improve quality control procedures by increasing operator training, and maximizing the inspection process in the inspection process. This recommendation is expected to improve the consistency of Drag Link product quality and reduce the defect rate, thereby strengthening the competitive position of PT. Indo Integral Sekawan in the automotive components market.